INTEGRATING TECHNOLOGY IN TEACHING AND LEARNING PROCESS: THE IMPLEMENTATION OF TRIPLE E FRAMEWORK IN TEACHING WRITING ARGUMENTATIVE ESSAY - Putu Ayu Paramita Dharmayanti; Dewa Ayu Ari Wiryadi Joni (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2026)
The aims of this study are to find out the lecturer’s perception on integrating technology in teaching and learning process and evaluate integration of technology in teaching writing argumentative essay. This research applied a case study method that focused on an individual lecturer at Universitas Mahasaraswati Denpasar. The subject of this study was a single subject that was selected purposively since that lecturer actively integrating technology in the teaching and learning process, especially in writing class. This research employed interview to know lecturer’ perception about integrating technology and classroom observation to get authentic data of integrating technology in writing class using Triple E framework rubric. Triple E Frameworks is one of framework that can be used to analyze and evaluate the effectiveness of technology integration in the teaching and learning process that focuses on how the integration of technology can help students to achieve learning goals. Based on the interview, it was revealed that the lecturer has positive perception toward the integration of technology in teaching and learning process. The results of observation indicate there was very strong connection between technology, instructional moves and learning goals. In detail, the technology integrated in teaching writing argumentative essay can engage students in learning and also enhance student learning to achieve learning goals. However, the integration of technology is still fairy less maximal for the purpose of extending the learning goals.